2009
DOI: 10.1057/hsq.2009.36
|View full text |Cite
|
Sign up to set email alerts
|

Demographic, behavioural and socio-economic influences on the survival of retired people - Evidence from a ten year follow up study of the General Household Survey, 1994

Abstract: This article reports on a longitudinal analysis of a sample of residents who were aged 65 or over when interviewed for the 1994 General Household Survey. It investigates the associations between various personal characteristics as established at the interview and the probability of survival during a ten year follow-up period. Smoking was the most important factor of those measured in determining the likelihood of survival. Smokers at the time of the interview had a mortality risk, on average, 78 per cent great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…it is a kind of weak proxy measure of accumulated human capital), and hence lifetime earnings. Final salary may therefore discriminate better between risk groups in the retired population than measures of current income or pre-retirement occupational status (Breeze et al 1999;Nazroo et al 2008;Johnson and Langford 2009). It is perhaps for this reason that final salary is a better predictor of mortality risk for male pensioners than Carstairs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…it is a kind of weak proxy measure of accumulated human capital), and hence lifetime earnings. Final salary may therefore discriminate better between risk groups in the retired population than measures of current income or pre-retirement occupational status (Breeze et al 1999;Nazroo et al 2008;Johnson and Langford 2009). It is perhaps for this reason that final salary is a better predictor of mortality risk for male pensioners than Carstairs.…”
Section: Discussionmentioning
confidence: 99%
“…Nor have such studies made much use of area-based measures of deprivation, presumably due to the sample sizes that are required for such analyses. Johnson and Langford (2009), in one of the few published studies which uses both socioeconomic and geographical variables in its analysis of influences specifically on mortality in the retired population, found that region appeared to have an effect on male mortality which was independent of socioeconomic position. Their sample, however, was small (approx.…”
Section: Introductionmentioning
confidence: 99%